Notes On A Rare Species From Turkey: Opopanax chironius - Mehmet Sağıroğlu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The first Turkish record of Opopanax chironius (L.) W.D.J. Koch was firstly collected from Tekirdağ province in 1969. The morphological description of the species in “Flora of Turkey and the East Aegean Islands” was written based on these specimens. The species has not been collected for along time untilday. This species was re-collected by us during a flora study in 2014 at Malkara district, Karaiğdemir Dam road in Tekirdağ. The name of this species was mispelled. This situation has been corrected here. Its correct use is Opopanax chironius. Also, in this study, expanded description of the species, pictures, disdictive morphological characters from other species, ecology, fruit photographs and ethnobotanical usage were given.